Determination of diffusion lengths in organic semiconductors: Correlation with solar cell performances - Longeaud, Christophe (2016)
Organic semiconductors are promising candidates for future applications in solar energy conversion. Recent investigations of bulk heterojunction (BHJ) semiconductors have suggested a density of states and transport mechanisms by multiple trapping close to those observed in disordered inorganic thin films. That is why we have applied to BHJ thin films experiments that are currently used for disordered semiconductors. In addition to the steady state photoconductivity we have tested the ability of the steady state photocarrier grating (SSPG) technique to provide information on the minority carrier diffusion length. We found that SSPG can be applied to P3HT:PCBM thin films leading, for the best sample, to a diffusion length of the order of 125 nm. From the comparison of the transport parameters obtained on thin films with the performances of the devices integrating the latter, we conclude that SSPG is a very powerful tool for optimizing the BHJ thin film properties before their incorporation in solar devices.